2018
DOI: 10.1186/s12967-018-1473-z
|View full text |Cite
|
Sign up to set email alerts
|

Weighting of orthostatic intolerance time measurements with standing difficulty score stratifies ME/CFS symptom severity and analyte detection

Abstract: BackgroundMyalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is clinically defined and characterised by persistent disabling tiredness and exertional malaise, leading to functional impairment.MethodsThis study introduces the weighted standing time (WST) as a proxy for ME/CFS severity, and investigates its behaviour in an Australian cohort. WST was calculated from standing time and subjective standing difficulty data, collected via orthostatic intolerance assessments. The distribution of WST for health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In view of the foregoing functional abnormalities in ME/CFS mitochondria, we tested the key elevated parameters ( Figure 5) for correlation with disease severity as assessed by the Richardson and Lidbury Weighted Standing Test [24]. We found that all were correlated with the clinical outcomes.…”
Section: Mitochondrial Abnormalities In Me/cfs Lymphoblasts Are Corrementioning
confidence: 99%
“…In view of the foregoing functional abnormalities in ME/CFS mitochondria, we tested the key elevated parameters ( Figure 5) for correlation with disease severity as assessed by the Richardson and Lidbury Weighted Standing Test [24]. We found that all were correlated with the clinical outcomes.…”
Section: Mitochondrial Abnormalities In Me/cfs Lymphoblasts Are Corrementioning
confidence: 99%
“…Patient subtyping to manage this heterogeneity has been previously discussed in the field [20,23] and is lent credence by reproduced patterns of differential disease-associated gene expression [24][25][26], gene expression profiles concurrent with comorbid POTS [27], distinct DNA methylation profiles associated with quality of life scores and PEM [28], severity and frequency of physical or mental fatigue [29], or irritable bowel syndrome (IBS) comorbidity [30] which can be concurrent with specific changes to patient metabolism [31]. As timely, objective and accurate diagnosis remains the most clear challenge facing the field, patient subtyping may be an important component of new diagnostic techniques and has seen early investigation with stratification-based severity scores [32] or cytokine co-expression patterns [33].In summation, ME/CFS etiology has been difficult to pin down due to the combination of a diagnostic quagmire and the disorder's heterogeneous symptom presentation across multiple body systems. A traditional view has held that ME/CFS onset is often precipitated by some manner of bodily insult, commonly infection, however the disorder is left without any known, single causative pathogen to date.…”
mentioning
confidence: 99%
“…Participants were selected using the Canadian Consensus Criteria [4] assessed for postorthostatic tachycardia syndrome comorbidity, and asked to complete the Depression, Anxiety and Stress Scale questionnaire and the Epworth Sleepiness Scale questionnaire. ME/CFS-specific severity assessments were also conducted using Richardson and Lidbury's weighted standing time [7]. For PBMC isolation, 15 mL of blood was taken per participant in heparin-treated vacutainer tubes (BD).…”
Section: Participant Cohortmentioning
confidence: 99%
“…To combat the subjectivity introduced by self-reported symptom scales, objective clinical measures have been explored previously, such as hand grip strength [6] or orthostatic intolerance and standing difficulty [7]. These physical measures have been demonstrated to have value in stratifying ME/CFS patients by disease state/severity and in aiding the separation of patients from healthy subjects.…”
Section: Introductionmentioning
confidence: 99%